Impact of bundled Climate-Smart Solutions (3S) on maize productivity and resilience across Agricultural Commercialization Clusters (ACCs) in Southern Ethiopia - Dejene, Sintayehu W; Alemayehu, Sintayehu; Tadesse, Terefe; Tesfaye, Lidya; Chilambe, Pedro; Girvetz, Evan (2025)
Maize production in Southern Ethiopia faces significant challenges from climate variability, including erratic rainfall, heat stress, and pest outbreaks, which constrain yields and threaten smallholder livelihoods. To address these challenges, the CGIAR Program on Scaling for Impact (SfI) piloted a bundled Climate-Smart Solutions (3S) package integrating climate risk profiling, context-specific CSA practices, access to finance, weather and climate information (WCIS) and agro-advisory services, and capacity-building interventions. This study assessed the impact of these bundled 3S on maize productivity and resilience among smallholder farmers across Agricultural Commercialization Clusters (ACCs) in south Ethiopia. A mixed-methods approach was applied, including a household survey of 600 farmers (150 CSA adopters and 150 non-adopters in 2025, plus 300 CSA farmers in 2024 as a baseline), focus group discussions, and systematic maize growth performance observations. Results indicated that CSA adopters in 2025 achieved an average yield of 36.33 quintal per hectare, representing a 45.65% increase from the 2024 (baseline) and 45.10% higher than non-adopters, who recorded 25.04 quintal per hectare. Field observations confirmed that bundled 3S enhanced germination, seedling vigor, vegetative growth, cob formation, and pest management, collectively strengthening resilience to climate variability. The study demonstrates that bundled 3S substantially improve maize productivity and strengthen smallholder farmers’ resilience to climate variability in Southern Ethiopia. By integrating climate risk profiling, context-specific CSA practices, access to finance, climate information and advisory services, and targeted capacity-building, the bundled 3S approach boosts maize yields, stabilizes production under climate variability, and strengthens adaptive capacity across farm systems. This approach has the potential to transform smallholder systems, enhance food security, safeguard livelihoods, and drive sustainable, climate-resilient agricultural development across ACCs. Importantly, the study also demonstrated evidence for scaling, showing that a fully integrated, locally tailored CSA package can be replicated across regions to achieve similar productivity gains and resilience benefits. Overall, the findings highlight that bundled 3S can serve as a scalable model for climate-resilient maize production, supporting sustainable agricultural intensification, improved food security, safeguarded livelihoods, and strengthened adaptive capacity among smallholder farmers.